Interpreting Shifts By Tour Guide At King Sidabutar’s Stone Tombs - Bambang Panca (EDUTECH, 2015)
The study aims at analyzing the process of interpreting shifts by a North Sumatera Tour Guide in consecutive interpreting at the ancient tomb of king Sidabutar. The interpreting study was focused on the two interpreting products from English into Indonesian and vice versa.The method used on this research was descriptive qualitative method. The data were obtained by applying some methods, i.e. observing the video, transcribing the utterances. The difference between the two language systems required the interpreter to apply some shifts; level shift, and category shift such as structure shift, unit shift, class shift and intra-system shift. Keywords: interpreting, shifts, interpreter.